2018
DOI: 10.4172/2161-1459.1000250
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Medication Adherence and its Association with Glycemic Control among Type-2 Diabetes Mellitus Patients in Gaza-Palestine

Abstract: Background: Diabetes mellitus is a serious health problem. It is considered the third leading cause of deaths among chronic diseases in the Gaza Strip, Palestine. Among diabetic patients, T2DM constitute the majority (92.2%). Medication adherence is a key determinant of therapeutic success. No studies have previously investigated medication adherence among T2DM patients in Gaza. Objectives: To assess medication adherence and its association with glycemic control among T2DM patients. Setting: Al-Rimal Martyr's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
5
5
0
1
Order By: Relevance
“…Consistently medication nonadherents also significantly reported in the previous studies (33)(34)(35). The most common reason for nonadherent was taking less medicine, stop taking medicine due to its adverse effects and forgetfulness, which was also consistent with the previous findings (11).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistently medication nonadherents also significantly reported in the previous studies (33)(34)(35). The most common reason for nonadherent was taking less medicine, stop taking medicine due to its adverse effects and forgetfulness, which was also consistent with the previous findings (11).…”
Section: Discussionsupporting
confidence: 89%
“…This study found a significant inverse relationship between high adherence scores and lower assayed values of HbA1C and FBS. Similar findings were also reported in the previous studies (11,32,44). In contrast to these findings, another study reported that medication adherence was not significantly associated with glycemic control status (45).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Poor medication adherence was also linked to higher HbA1c levels, and poor glycemic control in diabetic patients who participated in an Egyptian study [ 40 ]. Furthermore, glycemic control was found to be significantly affected by medication non-adherence among patients with type 2 diabetes who participated in several other studies conducted in Palestine [ 41 ], USA [ 42 ], China [ 43 ], and India [ 44 ]. Therefore, healthcare professionals should pay close attention to this problematic issue and exert efforts to solve it by implementing advanced strategies that aim at improving medication adherence through overcoming barriers to optimal medication adherence, and thus enhancing glycemic control in patients with type 2 diabetes, with special attention to those with additional comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Ketidakpatuhan yang tidak baik secara signifikan terkait dengan kontrol glikemik yang buruk (Viviandhari dkk., 2021). Buruknya kepatuhan terapi dipengaruhi oleh berbagai faktor, juga terkait dengan tingkat pengetahuan tentang DM yang rendah, pola diet yang tidak sehat, mitos yang beredar seputar diabetes serta testimoni masyarakat tentang diabetes (Almadhoun & Alagha, 2018) dan diperburuk dengan kondisi pembatasan kegiatan akibat pandemi COVID-19.…”
Section: Karakteristik Responden Penelitianunclassified